The Effect of Chitosan Addition to the Digestibility of Dried Matter, Organic Matter and Crude Protein of Tegal’s Duck Rations - Eli Sahara; Tuti Widjastuti; Rostita L Balia; Abun Abun (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The optimum performance of duck farm can be achieved by providing them with good quality rations. Rations with good digestibility will increase the productivity due to large amount intake of nutrients. Chitosan is type of animal fibre which assisted the growth of useful microbes in digestive system. Addition of chitosan in cattle rations will improve the ecologic of duck digestive system to be more conducive. The aimed of the research was to evaluate rations digestibility with the addition of chitosan. The research was used completely randomized design with 4 treatments and 5 repetitions. Each repetition consists of 2 ducks. The treatments are R0 stands for rations without chitosan and R1-R3 with addition of chitosan 0.5%, 2% and 2.5% respectively. Parameter measured were dried matter digestibility, organic matter and crude protein. Data processing was conducted by using SAS Windows 16. Result showed chitosan addition at 0.5% and 2.5% gave dried matter digestibility and crude protein does not higher than control (P>0.05) while chitosan addition at 2% gave result lower than control. Organic matter digestibility displays balanced in value.Keywords: Chitosan, Dried matter digestibility, organic matter, crude protein, rations.